Genetic susceptibility to aspergillosis in allogeneic stem-cell transplantation - Cunha, Cristina (2011)
Invasive aspergillosis (IA) is a major threat to positive outcomes for allogeneic stem-cell transplantation (allo-SCT) patients. Despite presenting similar degrees of immunosuppression, not all individuals at-risk ultimately develop infection. Therefore, the traditional view of neutropenia as a key risk factor for aspergillosis needs to be accommodated within new conceptual advances on host immunity and its relationship to infection. Polymorphisms in innate immune genes, such as those encoding TLRs, cytokines and cytokine receptors, have recently been associated with susceptibility to IA in allo-SCT recipients. This suggests that understanding host-pathogen interactions at the level of host genetic susceptibility will allow the formulation of new targeted and patient-tailored antifungal therapeutics, including improved donor screening.